Método y sistema para reducir tiempos de procesamiento de solicitudes en líneas de espera. - Pinto Serrano, Mario Augusto (Universidad Antonio Nariño, 2022)
Given that generally the customer service's resources cannot give service to all service demands, all the time, the queues are generated, also known as waiting lines. These queues are present in several aspects of the daily life. From a phenomenon present in optical communication systems, known as contention (When two or more packets are simultaneously at the same point), are proposed algorithms in order to deal with the contention. These algorithms are classified in two categories: pre-reservation and post-reservation. In the pre-reservation algorithms, the output channel is reserved before the packet ingress, in contrast with the pos-reservation algorithms, where the reservation is postponed, until after the ingress of the packet to the system. Based on the theoretical foundations of the post-reservation algorithms, and making abstractions of the used concepts, we propose a queue management system, focused on high complexity operative services, with high demands and interactions between the components